The Role of PPKN Teachers in Instilling Tolerance Values ​​at MA At-Tahzib - Dhea Kapril Amanda; Dewi Ratna Hidayati; Dimas Rinjani; Chelyna Ikthiari (Penerbit Presisi Pustaka, 2026)
This research aims to deepen understanding of the role of PPKn teachers in instilling the values of tolerance in the MA At-Tahzib environment in Kekait Village, Gunung Sari District, West Lombok Regency, West Nusa Tenggara. The research was conducted using qualitative methods with data collection techniques through field observations and in-depth interviews with PPKn teachers, to identify real practices, challenges and learning strategies used in building an inclusive school culture based on Pancasila values, especially the third principle, Indonesian Unity. The research results show that PPKn teachers play an important role as moral role models and facilitators of tolerance values through participatory learning methods such as class discussions, case studies, and project-based learning. A religious but open school environment also supports the formation of mutual respect between students. Apart from that, extracurricular activities such as scouting, social service, and OSIM are effective media in strengthening the value of tolerance outside the classroom. However, there are several challenges, including the negative influence of social media and the lack of integration of tolerance values between subjects. Therefore, cooperation between teachers and strengthening of cross-curricular activities is needed to ensure that the value of tolerance is not only taught cognitively, but also familiarized in everyday behavior.